Evaluation of Enrofloxacin and Toltrazuril residues in broiler muscles collected from Lattakia markets – Syria (Latakia University Journal -Biological Sciences Series, 2021)
This study aimed to evaluate the content of breast and thigh of broiler muscles from the antibiotic Enrofloxacin and anti-coccidia Toltrazuril, and to compare the results obtained, with the maximum residue limit (MRL) allowed locally and internationally, to assess the safety of human consumption of these meats.Random samples of broilers breasts and thighs were collected from the markets of Latakia during all months of 2018, and were extracted and analyzed in the laboratories of the Ministry of Agriculture in Damascus using the high-performance liquid chromatography technique (HPLC).      The results showed that there were high levels of Enrofloxacin and Toltrazuril in samples, ranging between (31.05 to 175.77 ) and (9.64- 251.09) µg/ kg, respectively. 79.2 and 87.5% of samples contained residues of them, and 41.67 and 50% of the total samples exceeded the maximum residues limit (MRL) for both Enrofloxacin and Toltrazuril, respectively. The statistical analysis of results showed no significant differences (P> 0.05) when comparing the mean concentrations of Enrofloxacin with each other during seasons. While the differences were significant (P≤0.05) when comparing the mean concentration of Toltrazuril in the second quarter samples with the mean concentration in the remaining quarters.